2018
DOI: 10.1186/s12885-018-4589-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum MMP-8 and TIMP-1 predict prognosis in colorectal cancer

Abstract: BackgroundAlmost all of the extracellular matrix (ECM) components can be degraded by the endoproteinases matrix metalloproteinases (MMPs). Important regulators of MMPs, and thereby of the extracellular environment, are tissue inhibitors of metalloproteinases (TIMPs), and especially TIMP-1. Early tumor development, as well as distant metastasis, may be results of an MMP/TIMP ratio imbalance altering the ECM. MMPs are elevated in several inflammatory conditions. Our aim is to investigate the prognostic role of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 38 publications
5
52
2
Order By: Relevance
“…MMP-2 in plasma increases with CRC tumour stage and there is a significantly higher concentration in the plasma of CRC patients compared to healthy controls 102 . Furthermore, the serum concentration of MMP-8 in patients with colorectal cancer has been found to correlate with survival 105,106 . Patients with CRC and a high expression of MMP-1 in tumour-free intestinal mucosa have poorer cancer-specific survival (CCS) compared to patients with low MMP-1 expression 107 .…”
Section: Matrix Metalloproteinases As Biomarkers In Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…MMP-2 in plasma increases with CRC tumour stage and there is a significantly higher concentration in the plasma of CRC patients compared to healthy controls 102 . Furthermore, the serum concentration of MMP-8 in patients with colorectal cancer has been found to correlate with survival 105,106 . Patients with CRC and a high expression of MMP-1 in tumour-free intestinal mucosa have poorer cancer-specific survival (CCS) compared to patients with low MMP-1 expression 107 .…”
Section: Matrix Metalloproteinases As Biomarkers In Colorectal Cancermentioning
confidence: 99%
“…In paper III the prognostic value of MMP measured in circulating plasma was evaluated and MMP-1 was found to have an impact of cancer specific survival. MMP concentrations in systemic blood have earlier been studied regarded colorectal cancer survival; this is shown in MMP-2, MMP-7, MMP-8 and MMP-9 where concentrations were measured in serum 101,105,106,139,140 . However, paper III studied levels of MMP in plasma samples that are known to be more stable than, serum 141 .…”
Section: Plasma Mmp Levels As a Prognostic Marker In Crcmentioning
confidence: 99%
“…While MMP 8 has been implicated in acute pancreatitis 39 its function in PDAC is unclear. A different study suggested that MMP8 could also function as a predictive biomarker in serum for colorectal cancer 40 . Another coding transcript, TBX3 is also highly represented in PDAC exosome compared to healthy and IPMN serum.…”
Section: Analysis Of Rna In Exosomes By Sequencingmentioning
confidence: 99%
“…Tissue inhibitor of metalloproteinases (TIMP-1), one of the most important regulators of matrix metalloproteinases (MMPs), is markedly increased in malignant tissue 18 and expressed in fibroblast-like cells located at the invasive front. 19 TIMP-1 is also associated with poor prognosis in colon cancer patients 20 and positively correlates with lymph node metastasis and Dukes classification. 21 TIMP-1 can promote the migration and invasion of cancer cells via reduction of cell apoptosis and activation of cell growth.…”
Section: Discussionmentioning
confidence: 98%